The Role of Purinergic P2 Receptors in the Skin Immune System - Al Kaff, Sahar (2011)
The skin performs a major role as a physical barrier to protect the body from environmental insults. In addition, the skin contains a network of immune cells, termed the skin immune system, to provide additional protection against such insults. There is emerging evidence that purinergic P2 receptors play an important role within the skin immune system. P2 receptors are divided into P2X receptors (P2X1-7) and P2Y receptors (P2Y1, 2, 4, 6, 8, 12, 13, 14), and are activated by extracellular ATP and other nucleotides. This review summaries the role of the skin immune system, and presents key findings regarding the expression and function of P2 receptors in this system. Information for this review was obtained by using ScienceDirect and PubMed databases, and by manually searching the reference lists of found studies. The findings show that various P2 receptors are present on a number of skin immune cells including keratinocytes, epidermal Langerhans cells, mast cells and fibroblasts. In particular, the P2X7 receptor plays a role in keratinocyte apoptosis, and in immune functions of Langerhans cells and fibroblasts, while mast cells express P2X1 and P2X4 but their functional role is remain unknown. In contrast, direct evidence for P2 receptors in other skin immune cells such as dermal dendritic cells, dermal macrophages, T cells and granulocytes is lacking. A role for these receptors in these cell types however can be inferred from studies of P2 receptors in equivalent cell types from the blood and other tissues. In conclusion, further studies examining the expression and function of P2 receptors on each skin cell type are required. Results from such studies will help in understanding the physiological and pathophysiological role of P2 receptors in the skin immune system.